Cluster-randomised trial evaluating a complex intervention to improve mental health and well-being of employees working in hospital - a protocol for the SEEGEN trial - Mulfinger, Nadine; Sander, Anja; Krisam, Regina; Maatouk, Imad; Helaß, Madeleine; Nikendei, Christoph; Küllenberg, Janna; Schweitzer, Jochen (BMC public health, 2019)
Health care employees in Germany and worldwide are exposed to a variety of stressors. However, most of the hospitals in Germany lack a systematic workplace health management. Thus, this study aims at the evaluation of the effects of a behavioural as well as organisational (´complex´) intervention on the mental health and well-being of hospital staff.